Sepsis-induced AKI: From pathogenesis to therapeutic approaches - He, Fang-Fang; Wang, Yu-Mei; Chen, Yi-Yuan; Huang, Wei; Li, Zi-Qi; Zhang, Chun (Frontiers in Pharmacology, 2022)
Sepsis is a heterogenous and highly complex clinical syndrome, which is caused by infectious or noninfectious factors. Acute kidney injury (AKI) is one of the most common and severe complication of sepsis, and it is associated with high mortality and poor outcomes. Recent evidence has identified that autophagy participates in the pathophysiology of sepsis-associated AKI. Despite the use of antibiotics, the mortality rate is still at an extremely high level in patients with sepsis. Besides traditional treatments, many natural products, including phytochemicals and their derivatives, are proved to exert protective effects through multiple mechanisms, such as regulation of autophagy, inhibition of inflammation, fibrosis, and apoptosis, etc. Accumulating evidence has also shown that many pharmacological inhibitors might have potential therapeutic effects in sepsis-induced AKI. Hence, understanding the pathophysiology of sepsis-induced AKI may help to develop novel therapeutics to attenuate the complications of sepsis and lower the mortality rate. This review updates the recent progress of underlying pathophysiological mechanisms of sepsis-associated AKI, focuses specifically on autophagy, and summarizes the potential therapeutic effects of phytochemicals and pharmacological inhibitors.